Influence of a functional core stability program on trunk and knee joint biomechanics in female athletes during lateral movements - Mornieux, G.; Weltin, E.; Friedman, C.; Pauls, M.; Forsythe, S.; Gollhofer, A. (The Journal of Strength and Conditioning Research, 2021)
Trunk positioning has been shown to be associated with knee joint loading during athletic tasks, especially changes of direction. Quasistatic and conventional core stability (CS) training did not improve the biomechanics of cutting maneuvers according to reports in the literature. The purpose of this study was to test whether a 5-week dynamic and functional CS training program would improve trunk positioning and knee joint control during lateral movements. Nineteen female athletes participated in a longitudinal study, where lateral reactive jumps (LRJs) and unanticipated cuttings were performed before and after CS training (15 training sessions within 5 weeks) while 3D kinematics and kinetics were measured. In addition, core endurance and power were evaluated. Core stability training increased trunk rotation in the new movement direction (p = 0.02) during LRJ. However, lateral trunk lean was significantly increased during LRJ (from 5.6 to 7°) and cuttings (from 3.8 to 5.8°) after CS training. Knee joint abduction moment was not influenced. Finally, core endurance (p < 0.01) and core power (p < 0.001) were significantly improved after CS training. A 5-week dynamic and functional CS training program improved core muscle endurance and power. This might explain the better trunk rotation toward the new movement direction during LRJ; however, it was not effective during unanticipated cuttings. The practical application of this research will allow strength and conditioning professionals to setup training programs with simple and relevant exercises to increase the core endurance and power of trained individuals.